Keretszélen körös-körül: Közép-Európa - Halmos, Károly (Tér és Társadalom, 1990)
Historians–little proudly–usually deflne Central Europe as a geographical dimension or history. The story is that of the West and it is about how the West has become the centre–not to say the middle–of the world. Given a historical region, it obviously has got a name. But it is not so sure that there is a civilization deposit, an all-overrunning and settled silt beneath the conceptual structures–which change over time–making up this name. Is there such a contiguous area or does such an area exist contiguously that we call Central Europe? The map on which we would draw the borders of Central Europe, upon request– allowing prudent people to hatchure a belt–, is a product unified by the science of centuries. An issueless map. If you read the instructions–learn to read the map–you can orientate on it. But our inner map of the surrounding world is different: based on the possibility of different mental maps, the paper suggests one in which distances are measured by ton-miles costs. The shape of the world in this map becomes similar to the one of Hekataios. The topology and geometry of this map are, however, non-Euclidian and discontinuous. Prior to railways, tree-shaped fluvial systems introduced a natural hierarchy or order among the points of space but railways–though often running along rivers–upset this natural arrangement. A developed i.e. dense road or rail network shrinks areas while the impact of a scarce one is similar to that of a caught thread in stockings: the whole netting would not get shrunk or „felted", only the thus far smooth „surface" would get disturbed along the wrested thread. Interdependent regions would increasingly fall into micro-regions, drifting extremes closer to each other, creating inequalities even within relatively small areas–like when you flash past a bidonville along the highway. The aim of the present paper is twofold: It was intended to highlight the fact that a regional view pre-suggests some kind of dominant unity, therefore the answer lies, from many aspects, in accepting the question. It was intended to contribute to making previous questions trivial and previous trivialities questionable by suggesting a map which is different from the usual one. As for the author, he would be contended if Central Europe were not only a „historical concept" but also „constructed by history".